(untitled) (Journal of Agriculture and Plant Sciences, 2013)
This paper describes the two-year research on exploitation parameters of the machine for tillage of soil in a row, in vineyard. We made examinations of the exploitation parameters of the special plough LEMENS, aggregated with NEW HOLLAND 65-56 tractors. We can fi nd out from the results and discussion in this paper how big is the production of this type of machine, how much the oil costs, as well as the economic parameters of this type of machine.